An Analysis On The Emotional interactions Of Light And Color: The Visual Culture Of Istanbul - Manav, Banu; Kutlu, Rana; Ormancı, Sevinç (Medimond S R L, Via Maserati 5, 40128 Bologna, 00000, Italy, 2012)
The abstract composition of colored light, color appearance of surfaces, color-mood associations may give rise to subjective evaluations in a space. Light can affect human nervous system, cognition, memories, expectations and this spiritual energy is vital for our lives. Light is also an energy which provides a balance via the complementary of opposites, expressed in terms of yin and yang. Yin and yang together make up the wholeness of the universe, for without one the other cannot exist. The present study discusses the importance of light energy and color composition in the historical background of three renovation projects in Istanbul. Also, the spiritual power of light-color are explained by means of the complementary of these two opposite poles; yin and yang. The superimposed images of light and color are analyzed from the view point of emotional interactions of light and color in design concept. The sign-function of light and color symbolism are also discussed by means of the transformation of cultural heritage of the historical image to their new cultural identity.
Keywords: light; color; emotional interaction; visual culture; ışık; renk; duygusal etkileşim; görsel kültür